Nonsingular Fast Terminal Sliding Mode Controller for a Robotic System: A Fuzzy Approach - Alnufaie, Lafi (Engineering, Technology & Applied Science Research, 2023)
This study presents a combination of Type-2 fuzzy logic and nonsingular fast sliding mode technique to design a robust controller for a robotic system. The control law is composed of two signals. The first one called equivalent control law is dedicated to maintaining the system on the sliding surface and then converges to zero. Since the system is uncertain, a Type-2 fuzzy nominal model was constructed, deduced from linear local models, which allows a good approximation of the real robotic system. The second signal, whose objective is to force the system to attain the sliding surface, is deduced from stability analysis using Lyapunov theory. Several simulations were conducted to evaluate the efficiency of the proposed approach, showing good tracking performance for different reference signals despite the presence of uncertainties and external disturbances.